Pelatihan Kebersihan Lingkungan Rumah Tinggal sebagai Upaya Pencegahan Penyakit di Desa Ganting Damai - Desrimon, Arfi; Setiawan, Beny; Lelis Febrianty, Nanda (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2025)
A clean home environment is a crucial factor in preventing various environmental-related diseases such as diarrhea, skin diseases, respiratory infections, and digestive disorders. The low level of awareness among the people of Ganting Damai Village regarding environmental hygiene has led to the continued presence of poorly managed waste disposal, a lack of sanitation facilities, and a lack of knowledge about clean and healthy living practices. This community service activity aims to provide training and assistance to the community to ensure they are able to maintain a clean home environment sustainably. Implementation methods include outreach, interactive discussions, and demonstrations on waste management, sanitation, and the use of existing sanitation facilities. The results of the activity indicate an increase in community understanding regarding the importance of environmental cleanliness as well as changes in behavior regarding the use of sanitation facilities and household waste management. This training is expected to be the first step in reducing the incidence of environmental-related diseases and can be used as a model for community empowerment in other areas.